2021
DOI: 10.1093/ptj/pzab092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Interventions on Aerobic Capacity and Health-Related Quality of Life in People Living With HIV/AIDS: Systematic Review and Network Meta-Analysis

Abstract: Objective Exercise is a recommended component of care for people living with HIV/AIDS; however, it is unclear which type of exercise is most effective. The purpose of this study was to investigate the relative effects of different types of exercise interventions on aerobic capacity measured by peak oxygen consumption (peak VO2) and health-related quality of life (HRQoL) in this population. Methods For this systematic review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
0
10
0
1
Order By: Relevance
“…Our review could not confirm that physical activity interventions had significant effects on psychological profiles, including health-related quality of life and depression. A previous review reported that the combined aerobic and resistance exercise was the most effective exercise type for improving health-related quality of life for people living with HIV [ 45 ]. In addition, a different review reported that there were large effects on depression improvement in people living with HIV with an aerobic exercise intervention, three or more times per week, supervised by a professional [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our review could not confirm that physical activity interventions had significant effects on psychological profiles, including health-related quality of life and depression. A previous review reported that the combined aerobic and resistance exercise was the most effective exercise type for improving health-related quality of life for people living with HIV [ 45 ]. In addition, a different review reported that there were large effects on depression improvement in people living with HIV with an aerobic exercise intervention, three or more times per week, supervised by a professional [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…41,42 A more recent meta-analysis found that combined aerobic and resistance training was the most effective exercise intervention to improve cardiorespiratory fitness and health-related quality of life. 43 In addition, Ghayomzadeh et al found that combined training in PLWH increased muscle mass, reduced circulatory levels of pro-inflammatory cytokines and improve muscle function. 3 Additionally, there were a number of par-ticipants with pre-sarcopenic conditions in the combined training group where this condition was reversed while no change occurred in the control group.…”
Section: Sarcopenia Reducing Factorsmentioning
confidence: 99%
“…In our study, we addressed the need of incorporating PA in the comprehensive care provided to PLH and the challenges for its effectiveness from the perspective of patients followed up at a university HIV outpatient clinic in the city of São Paulo, Brazil. Our option to evaluate this relevant issue among PLH starting ART without body changes and metabolic abnormalities was due to the fact the PA has already been well recognized as useful to treat these longterm adverse effects of chronic HIV infection and ART [7][8][9][10][11][12][13]26]. In contrast, our main interest was to understand to what extent promotion of PA could benefit individuals at early stages of HIV infection and what services could do to maximize intervention uptake.…”
Section: Plos Onementioning
confidence: 99%
“…In fact, there is evidence that combined resistance and aerobic training improve body composition, increase muscular strength, and reduce blood cholesterol of PLH [7][8][9]. In addition, training leads to increased cardiorespiratory fitness and flexibility of these patients [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%